Respiratory morbidity in late preterms - A retrospective study in a tertiary care centre - Varsha Muddasani; K. Shreedhara Avabratha (Al Ameen Medical College, 2019)
Introduction: Late preterm births are defined as births at 340/7 through 366/7 weeks of gestation, and account for 6.87% of all births. Most often late preterms are considered as healthy as full term babies ignoring the fact that they are physiologically immature and are at a higher risk of morbidity and mortality. Objective: To study the respiratory morbidity in late preterms. Methodology: This is a retrospective study done at a medical college hospital in Mangalore. Data was obtained from case sheets in Medical Records Department of the hospital and entered into predesigned proformas. Results: There were 135 Late Preterm Births (LPB) admitted in the NICU in the study period of which 114 met the inclusion criteria. Out of the 114 LPB maximum belonged to the gestational age of 34 weeks (42%) and least in 37 weeks (10%) of gestation. Ninety three babies had NICU admissions for respiratory Morbidities. Retractions being the most common clinical presentation, with 69% (n=79)of babies presenting with this symptom followed by tachypnea and grunt both being present in 46%(n=52) of the babies. Each symptom was analysed for each corresponding Gestational week, and it was found that retractions and grunt were highly significant. Tachypnea was not found to be statistically significant. It was found that 67 babies required CPAP, 15 babies' required hood box oxygen, and 13 babies required to be mechanically ventilated to attain stable status. Maximum babies were diagnosed with RDS, followed by TTN and Apnea of prematurity. RDS compared to gestational week, showed the descending pattern with advancing gestational week. There were 2 mortalities of babies born in the gestational week of 34 weeks. No deaths were found in the subsequent weeks. Average length of stay was found to be less than 10 days in all weeks except LPB born by 34 weeks that needed longer lengths of hospital stay extending to 20 days. Conclusions: Our study shows increased respiratory morbidity with decreasing weeks of gestation. It is imperative that while dealing with late preterms these aspects need to be kept in mind.